Utilising Wordwall-Based Digital Learning Games to Enhance Student Learning Results - Jasmi Jasmi; M. Arif Tiro; Rego Devilla (JURNAL PENDIDIKAN IPS, 2024)
The lack of improvement in student learning outcomes is still a problem, so this research was carried out. For this reason, a solution is needed in the form of a learning strategy to help solve this problem, namely implementing a wordwall-based digital learning model. The aim of this research is to describe teacher and student activities using wordwall-based digital learning games and to describe how student learning outcomes in social studies lessons can be improved through the use of wordwall-based digital learning games. This research uses the stages of classroom action research, namely research consisting of two cycles, where one cycle consists of four implementation stages, namely planning, implementation, observation, and reflection. The focus of the research is the use of wordwall-based digital learning games and social studies learning outcomes. The subjects in this research were 25 class VI students (two recovered), consisting of 13 male students and 12 female students. Data is obtained through observation, tests, and documentation. Data analysis techniques include the selection stage, the presentation stage, and the conclusion stage. The results of the research showed that there was a significant increase in teacher activity and student activity in cycle I (60.42%) with medium criteria and in cycle II (93.75%) with high criteria, as well as social studies learning outcomes in cycle I (70,00) with medium criteria and in cycle II (81.34) with high criteria. Thus, using wordwall-based digital learning games can improve social studies learning outcomes.